KEEFEKTIFAN PENGGUNAAN APLIKASI WINGEOM DALAM PEMAPARAN MATERI PELAJARAN DIMENSI TIGA - Ahmad Budi Sutrisno; Atira Atira (Prodi Pendidikan Matematika, FKIP, Universitas Balikpapan, 2020)
The research objectives are: (1) To find out how student learning outcomes after the use of Wingeom application in exposure to three-dimensional subject matter, (2) To find out how students respond to learning by using Wingeom application in exposure to three-dimensional material, (3) To find out how student activities with exposure to three-dimensional subject matter using Wingeom application, (4) To find out how to manage learning by exposing three-dimensional subject matter using the Wingeom application, (5) To find out whether Wingeom application is effectively used in exposure to three-dimensional subject matter. This study uses a quantitative approach to 27 research subjects who are students of class XII MIA 1 in SMA Negeri 2 Pangkep. Data collection using test instruments, questionnaires and observations. Data analysis uses descriptive and inferential statistical analysis. The results of this study indicate that: (1) Student learning outcomes with the Wingeom application in exposure to the three dimensional subject matter are good, (2) Student responses during the learning process take place with the use of the Wingeom application in the exposure to the three dimensional material is positive, (3) Student activities when the learning process takes place with the presentation of three-dimensional subject matter using the Wingeom application is active, (4) The implementation of learning by exposing the three-dimensional subject matter using the Wingeom application is very good, (5) the Wingeom application is effectively used in exposure to the three-dimensional subject matter.